Prevalence and Effects of Gestational Diabetes Mellitus on Pregnancy and Foetal Outcomes among Women Attending Health Clinic in Perak - Pachiamma Nahappan; Osman Ali (Asian Journal of Medicine & Health Sciences, 2022)
Background: Gestational Diabetes Mellitus (GDM) is known to affect the livelihood of the mothers and the baby before, during and after the pregnancy. The incidence seems to be on the rise worldwide and has increased the disease burden of the population. Objectives: The aim of the cross-sectional study was to determine the association between various factors during antenatal, intrapartum, and postpartum with the prevalence of GDM among mothers at one of Kinta District’s health clinics. The impact of gestational diabetes mellitus (GDM) on the newborns was documented. Methodology: This study was done among mothers who registered at the health clinic from January 2016 to December 2017. Systematic random sampling was used to select 300 antenatal records from the health clinic’s repository. Socio-demographic, behavioural characteristics, reproductive and medical history were extracted from these records. The data were analysed using SPSS to identify various factors associated with GDM. Results: The prevalence of GDM in this study was 22.6% and more often developed in the second semester of the pregnancy. There was a significant association between a prevalence of GDM with weight during a pregnancy booking, maternal obesity, history of either GDM, abortion (2 times or more), urinary tract infections, LSCS or medical problems in a family (p<0.05). During delivery, uterus bigger than date seem to be very significant association with GDM. Wound breakdown was the only post-partum factor that has a significant association with GDM. Severe jaundice occurred more frequently in neonates in mothers with GDM (58.3%) than in mothers without GDM. Conclusion: The prevalence of GDM was high among women attending health clinic in Perak. It affects the health of mothers, foetuses, and neonates. Measures are needed to control GDM to reduce its impact on health of the mothers and survival of the infants.